2021
DOI: 10.3390/ijerph18115641
|View full text |Cite
|
Sign up to set email alerts
|

Using the Water and Sanitation for Health Facility Improvement Tool (WASH FIT) in Zimbabwe: A Cross-Sectional Study of Water, Sanitation and Hygiene Services in 50 COVID-19 Isolation Facilities

Abstract: The availability of water, sanitation and hygiene (WASH) services is a key prerequisite for quality care and infection prevention and control in health care facilities (HCFs). In 2020, the COVID-19 pandemic highlighted the importance and urgency of enhancing WASH coverage to reduce the risk of COVID-19 transmission and other healthcare-associated infections. As a part of COVID-19 preparedness and response interventions, the Government of Zimbabwe, the United Nations Children’s Fund (UNICEF), and civil society … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 15 publications
(15 reference statements)
0
16
0
Order By: Relevance
“…According to the WHO standard, functional hand hygiene facilities should be available at all critical points of the HCFs [7]. Less than a quarter (21.4%) of the HCFs had functional handwashing facilities (with water and soap) both in latrines and at point of care, which was lower than the studies conducted in Africa (28%) [41], Zimbabwe (30%) (26), LMICs [12], sub-Saharan Africa (67%) [8], Rwanda (32%) [40], Nigeria (66%), Rwanda (65%), Zimbabwe (58%) [7] and Ethiopia (74.28%) [44] but higher than Niger (4%) [7].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…According to the WHO standard, functional hand hygiene facilities should be available at all critical points of the HCFs [7]. Less than a quarter (21.4%) of the HCFs had functional handwashing facilities (with water and soap) both in latrines and at point of care, which was lower than the studies conducted in Africa (28%) [41], Zimbabwe (30%) (26), LMICs [12], sub-Saharan Africa (67%) [8], Rwanda (32%) [40], Nigeria (66%), Rwanda (65%), Zimbabwe (58%) [7] and Ethiopia (74.28%) [44] but higher than Niger (4%) [7].…”
Section: Plos Onementioning
confidence: 99%
“…In May 2019, the World Health Assembly passed a resolution to accelerate global efforts on WASH in HCFs. This resolution led to a subsequent global meeting where countries presented their national commitments with concrete actions [26]. The government of Ethiopia has also implemented various COVID-19 prevention measures, such as partial or total lockdown, physical distancing, handwashing, and others [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Only 8% of the facilities scored good and 42% scored poor in WASH domains. 27 However, some studies in developed countries, including the United States, reported the need for improvement in adherence to COVID-19 IPC measures. For instance, a study in the state of Georgia assessed adherence to IPC guidelines in 24 health facilities and classified them into higher and lower prevalence facilities depending on the prevalence of COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%
“…These are more likely to affect the dignity and privacy of users. Unavailability of insufficient gender-sensitive sanitation facilities, the menstrual hygiene toilets, was also shown in is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) studies conducted in Uganda and Zimbabwe (21,24), the proportion of sanitation facilities for menstrual use and disabled user remains poor. This could be due to that the essence of WASH for all might not be given emphasis and the design of the facility not considering user sensitive sanitation facility.…”
Section: Discussionmentioning
confidence: 99%